Influence of the nuclear electric field on processes of annihilation of positrons emitted at β+-decay - S. N. Fedotkin (Ядерна фізика та енергетика)
The process of atomic shell ionization during annihilation of positron, emitted at β+-decay, with K-electron of daughter's atom is considered. The role of nuclear Coulomb field at calculation of the probability of this process is investigated. It is shown that the correct account of the influence of this factor on the states of electron and posi-tron changes the probability of atomic ionization appreciably. The ratio of the probabilities of processes of atom-ic ionization and usual β+- decay is notably changed.